2019
DOI: 10.1016/j.jsxm.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Treatment Effect on Sexual Distress in Transgender Persons: 2-Year Follow-Up Data

Abstract: Introduction As far as we know, no studies to date have investigated the psychobiological correlates of sexual distress (SD) nor the impact of hormonal treatment (HT) on SD in transgender persons. Aim To evaluate the psychobiological correlates of SD and assess the effects of HT on SD in transgender persons without gender-affirming surgery. Methods A consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 37 publications
0
20
0
5
Order By: Relevance
“…This may mean that gender diversity in developmental age receives less attention than it deserves. However, despite the apparently low numbers of referrals and centers compared with other countries, the improved diagnostic accuracy and the intensified resonance and media visibility of transgender lives have led to an increase in Italian studies on this topic (Amodeo et al, 2018; Fisher et al, 2013; Giovanardi et al, 2018, 2019; Lingiardi et al, 2017; Ristori et al, 2020; Scandurra et al, 2018; Vitelli et al, 2017; Vitelli & Riccardi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This may mean that gender diversity in developmental age receives less attention than it deserves. However, despite the apparently low numbers of referrals and centers compared with other countries, the improved diagnostic accuracy and the intensified resonance and media visibility of transgender lives have led to an increase in Italian studies on this topic (Amodeo et al, 2018; Fisher et al, 2013; Giovanardi et al, 2018, 2019; Lingiardi et al, 2017; Ristori et al, 2020; Scandurra et al, 2018; Vitelli et al, 2017; Vitelli & Riccardi, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In their individuation process, participants conferred a fundamental role to medical-surgical treatments for gender affirmation (e.g., access to hormones and surgery), which represented methods for bringing one’s gender expression closer to one’s gender identity [ 44 , 45 ]. Medical-surgical treatments have long had gender affirming value for many transgender people [ 46 , 47 , 48 , 49 ]. Specifically, hormones and surgery are the medical means by which many transgender people achieve psychophysical wellbeing.…”
Section: Resultsmentioning
confidence: 99%
“…In achieving psychological wellbeing and quality of life, many transgender and non-binary people find hormone therapies and gender affirming surgery essential. Indeed, through these medical-surgical treatments, many transgender people achieve wellbeing and fulfillment and a more positive identity [ 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Psy et al reported that hormone therapy significantly ameliorated sexual distress evaluated by the Female Sexual Distress Scale-Revised in both transgender men and transgender women. 13 Increased body hair density evaluated by the Ferriman-Gallwey Score in transgender men and prominent breast growth evaluated by the Tanner stage in transgender women were involved in decreased sexual distress. However, very few studies showed what effects induced by hormone therapy using gender-affirming hormones mainly contribute to improvement in the quality of life through reduction of gender dysphoria.…”
Section: Discussionmentioning
confidence: 99%